Best practice in license allocation in the oil and gas industry: A review of five countries. (December 2021) - Cillari, Azzurra; Stephens, Sian; Werner, Andrea
Abstract: The implementation of good practice in the natural resource management processes is crucial to the economic development of many countries. Well managed resources can bring high financial rewards and benefit the entire country, while poor resource management can lead to severe social and economic consequences. The allocation of licenses for the exploration and development of the natural resources is of particular importance in establishing good management and ensuring the accrual of benefits to the country. In this paper we identify an analytic framework for establishing the most suitable license allocation approach in any context, and apply this to five case studies. From this application we draw conclusions regarding best practice and identify the policy implications of this discussion. Highlights: The Oil and Gas licensing strategies are Direct Negotiation and Licensing Rounds. Establish good practice is crucial for the economy of developing countries. Licensing strategies examples from Egypt, Mozambique, Tunisia, Jamaica, Sri Lanka. Outcomes of cases study are frequently not the expected ones. There are internal barriers in the application of good practices.